Phase morphology and mechanical properties of rubber-toughened polypropylene nanocomposites: Effect of elastomer polarity - Lim, Jian Wei; Hassan, Azman; Rahmat, Abdul Razak; Wahit, Mat Uzir (Elsevier B.V, 2008)
The objective of this work was to investigate the effect of elastomer polarity on phase structure and mechanical properties of PP nanocomposites. The nonpolar and polar elastomers studied were polyethylene octene (POE) and polyethylene octene grafted maleic anhydride (POEgMAH), respectively. The results from mechanical studies showed that the POEgMAH-toughened polypropylene nanocomposites have higher Izod impact strength but lower tensile and flexural properties than the unmaleated ones. X-ray diffraction (XRD) was used to characterize the formation of nanocomposites. XRD studies revealed that intercalated rubber-toughened PP nanocomposites (RTPPNC) had been successfully prepared where the macromolecule segments PP were intercalated into the interlayer space of organoclay. XRD also indicated that the incorporation of polar POEgMAH elastomers into PP nanocomposites contribute to a better intercalation effect and formed a more exfoliated combinations structure compared to POE. Scanning electron microscope (SEM) was used for the investigation of the phase morphology and rubber particle size and particle-size distribution. SEM study revealed a two-phase morphology where POE as droplets dispersed finely and uniformly in the PP matrix. The POEgMAH-toughened PP nanocomposites shows a much finer dispersion of elastomer particles than POE-toughened PP nanocomposites.